2013
DOI: 10.1002/phar.1345
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Dosing in Children and Young Adults: Back to the Drawing Board

Abstract: BSA-based dosing is more likely than weight-based (mg/kg) dosing of vancomycin to achieve isometric AUC24 values across the body size distribution of children and young adults. Pharmacokinetic studies that compare these two vancomycin dosing strategies in children are clearly needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In contrast, most pediatric studies reported no clinically significant differences in the PK parameters between obese and nonobese children . Based on Bayesian PK analysis, Vd is strongly correlated with TBW and Cl, with ALW and BSA …”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, most pediatric studies reported no clinically significant differences in the PK parameters between obese and nonobese children . Based on Bayesian PK analysis, Vd is strongly correlated with TBW and Cl, with ALW and BSA …”
Section: Methodsmentioning
confidence: 93%
“…Vancomycin is perhaps the most studied antimicrobial agent in obese children and adults . PK studies suggest a strong correlation between Vd and Cl with TBW in obese adults .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearance was best described using TBW to the power of 0.75, also known as allometric weight (37). In another analysis of 115 children and adolescents over a wide spectrum of body sizes, Camaione and colleagues (38) speculated that defining a desired target range for area‐under‐the‐concentration‐time curve (AUC) might be worth exploring as an alternative to target drug concentrations (i.e., peak and trough). They also proposed body surface area as an alternative to body weight.…”
Section: Findings and Discussion By Therapeutic Categorymentioning
confidence: 99%
“…The fourth article by Dr. Lauren Camaione and colleagues evaluated vancomycin dosing and pharmacokinetics in 115 children and young adults who each had 2–9 serum concentration measurements . These investigators employed a previously described one‐compartment pharmacokinetic model to derive individual maximum a posteriori probability (MAP)‐Bayesian pharmacokinetic parameter estimates and to evaluate covariate relationships of body size descriptors (weight, height, and body surface area [BSA]).…”
mentioning
confidence: 99%